2017
DOI: 10.1177/1010539517717366
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Direct Medical Economic Burden of Health Care–Associated Infections in Public Tertiary Hospitals in Hubei Province, China

Abstract: This study estimated the attributable direct medical economic burden of health care-associated infections (HAIs) in China. Data were extracted from hospitals' information systems. Inpatient cases with HAIs and non-HAIs were grouped by the propensity score matching (PSM) method. Attributable hospitalization expenditures and length of hospital stay were measured to estimate the direct medical economic burden of HAIs. STATA 12.0 was used to conduct descriptive analysis, bivariate χ test, paired Z test, PSM ( r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Currently, there are few economic studies about HAI in Mainland China. Studies from Hubei and Sichuan demonstrated that the attributable cost of HAI were US$6173.02 and $2439.77 per case, respectively [13,14]. Another Chinese study of catheter-related bloodstream infections indicated the total cost attributable was US $3528.6 per case [15].…”
mentioning
confidence: 99%
“…Currently, there are few economic studies about HAI in Mainland China. Studies from Hubei and Sichuan demonstrated that the attributable cost of HAI were US$6173.02 and $2439.77 per case, respectively [13,14]. Another Chinese study of catheter-related bloodstream infections indicated the total cost attributable was US $3528.6 per case [15].…”
mentioning
confidence: 99%
“…On the other hand, a statistical report of traffic accidents or an epidemiological investigation of factors related to the traffic accidents at the local level will not be considered as global. Studies conducted in a local hospital on drug resistance to antibiotics and associated cost are global if expected findings can inform other countries to prevent abuse of antibiotics [77]. Lastly, studies supported by international health programs can be packaged as global simply by broadening the vision from international to global.…”
Section: Reframing a Local Research Study As Globalmentioning
confidence: 99%
“…Both of them are associated with increasing mortality, morbidity and length of hospitalization (5). Eventually, there is an increasing economic burden on society, patients and their family (6)(7)(8). In the United States, the annual approximate number of deaths caused by HAIs was 90,000 from 1990 to 2002, corresponding to US$ 28 to US$ 45 billion per year (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is the rst time to apply our research team's previous estimation framework to estimate the economic burden due to HAIs and AMR in a teaching hospital of Nepal. The framework was designed to calculate the direct economic burden attributable to HAIs and AMR in Hubei Province, China given the support from the UK (6). The idea was put forward because of the 'One Belt, One Road' initiative proposed by Chinese President Xi in 2013, aiming to improve cooperative relationship with countries included in this initiative (12).…”
Section: Introductionmentioning
confidence: 99%